Principles for innovation management in family firms: An analysis of long-term successful good practices with a practitioner validation of the principles. Issue 3 (2nd September 2019) - Frank, Hermann; Kessler, Alexander; Bachner, Christine; Fuetsch, Elena; Suess-Reyes, Julia
Abstract : Purpose: Family firms (FF) reveal a considerable heterogeneity in their innovation behavior. Due to the successful long-term preservation of their innovation capacity via special resources and routines, multi-generational FF are of special interest in terms of learning from good practices. Against this background, the purpose of this paper is to ascertain principles for successful innovation behavior in long-term successful FF and to contribute to bridging the theory-practice gap. Design/method/approach: Results are generated by analyzing innovation and innovation processes in five cases of long-term successful FF. On the basis of these good practice cases, the "rules of the game" of innovating are re-constructed using fine and system analyses based on narrative interviews with the FF CEOs. Findings: Intense reflection on the innovation characteristics of the five good practice cases along with a critical examination of the literature on innovation in FF were used to derive practical suggestions for FF in the form of 11 principles for FF taking a proactive interest in innovation. Practical implications: The 11 generated principles of successfully innovative FF were validated by FF CEOs who confirmed the practical relevance of these principles as valuable guidelines for successful innovation. Owners and managers may reflect on these principles against the background of the innovation behavior of their firms and adapt them to their contextual conditions. Originality/value: These principles serve as tangible suggestions for developing adequate innovation management strategies for individual FF. Furthermore, two FF CEOs were invited to comment on the viability of principles based on their comprehensive practical experience.